THE WORKS OF Z. M. BABUR IN UZBEK POETRY. - Saidmuradova Sakhiba Jalmuradovna; Sattorova Surayyo Alisher qizi (TADQIQOTLAR.UZ, 2024)
Abstract. The article discusses the spirit of the work of Zahiriddin Muhammad Babur, the most prominent representative of Uzbek literature after Alisher Navoi, the state and public figure, the "Hatti Baburii" alphabet, and the writer's contribution to the development of the rubai genre.